2021
DOI: 10.1177/15266028211007469
|View full text |Cite
|
Sign up to set email alerts
|

Technical Aspects of Fenestrated Arch TEVAR With Preloaded Fenestration

Abstract: Fenestrated thoracic endovascular aortic repair (f-TEVAR) has expanded the possibilities of endovascular arch repair, allowing treatment of pathologies involving the aortic arch that require sealing in Ishimaru zones 1 and 2. The growing number of implantations has increased physician experience and helped identify critical procedural points, mainly wire entanglement and device malrotation. Herein we describe a step-by-step approach to a f-TEVAR procedure with the Zenith fenestrated preloaded thoracic endograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Chassin-Trubert et al reported improvement in the success rate after applying the pre-loaded guidewire [from 94% (19/22) to 100% (28/28)], all of which were total endovascular aortic arch repair, revascularizing all supra-aortic trunks ( 22 ). Additionally, the alignment could be simplified and reassured with a pre-loaded guidewire, thus shortening the learning curve ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chassin-Trubert et al reported improvement in the success rate after applying the pre-loaded guidewire [from 94% (19/22) to 100% (28/28)], all of which were total endovascular aortic arch repair, revascularizing all supra-aortic trunks ( 22 ). Additionally, the alignment could be simplified and reassured with a pre-loaded guidewire, thus shortening the learning curve ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of endografts, some authors have advocated the use of preloaded through-and-through guidewires through the LSA for endovascular aortic arch repair. [2][3][4][5][6][7][8][9][10] Some of these devices are fenestrated, associated or not with scallops or larger fenestrations, while others consist of inner or outer branches. All of them share the technical potential obstacle of wire wrapping.…”
Section: Discussionmentioning
confidence: 99%
“…These maneuvers involve partial deployment of the devices, rotation, and retraction in the aortic arch prior to full deployment. 8,9 This manipulation is fraught with device distortion, failure to cannulate a fenestration, cerebral embolization, or failure to advance the graft without losing preloaded guidewires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Commonly, OAR is reserved only for those fit patients in experienced highvolume centres and TEVAR arises as the best treatment for those anatomically suitable. 6 Many techniques have been described to achieve adequate proximal/distal landing zones (PLZ/DLZ); as scallops, 7 chimneys, 8,9 in-situ laser fenestration, 10 endograft modifications, 11 branched repair, 12 fenestrated repair 13 and hybrid procedures associating cervical supra-aortic debranching. These approaches are critical to optimising the length of the LZ in order to minimise the risk of type I endoleaks (T1ELs).…”
Section: Introductionmentioning
confidence: 99%